Management of Patients with Systemic Sclerosis-Associated Interstitial Lung Disease: A Focus on the Role of the Pharmacist - Farrell J; Ho L (Dove Medical Press, 2023)
Jessica Farrell,1 Lawrence Ho2 1Albany College of Pharmacy and Health Sciences and Albany Medical Center Division of Rheumatology, Albany, NY, USA; 2Center for Interstitial Lung Disease, University of Washington, Seattle, WA, USACorrespondence: Jessica Farrell, Albany College of Pharmacy and Health Sciences and Albany Medical Center Division of Rheumatology, Albany, NY, USA, Email Jessica.Farrell@acphs.eduAbstract: Interstitial lung disease (ILD) is a common manifestation of systemic sclerosis (SSc), which becomes fibrosing and progressive in some patients. Regular monitoring of patients with SSc-ILD is important to assess progression and inform treatment decisions. Therapy for SSc-ILD may include immunomodulatory and antifibrotic therapies. Therapeutic decisions should be made on a case-by-case basis, ideally following multidisciplinary discussion. Most patients with SSc-ILD have several organ manifestations of SSc or comorbidities and are taking a complex medication regimen. Patients with SSc are particularly susceptible to gastrointestinal side-effects of medications due to the gastrointestinal manifestations of the disease. Pharmacists play an important role in the management of patients with SSc-ILD by assisting patients with access to medications, optimizing medication regimens, and advising on alternative dosage forms. Pharmacists can also contribute to patient education to help patients better understand their treatment and how to prevent and manage potential side effects.Keywords: immunosuppressants, lung disease, pulmonary fibrosis, scleroderma, therapeutics